Antimicrobial and antibiofilm activity of Cymbopogon flexuosus essential oil microemulsions - Dalla Costa, Karine Angélica; Moura, Renata; F. Millezi, Alessandra (Revista Ceres, 2025)
The objective of the study was to determine the antimicrobial activity antibiofilm and to identify the main components of the essential oil (EO) obtained from the leaves of Cymbopogon flexuosus. The antibacterial and antibiofilm activity was determined against Staphylococcus aureus ATCC 29213, Pseudomonas aeruginosa ATCC 27853, Salmonella Typhimurium ATCC 14028 and Listeria monocytogenes ATCC 19117. The effect of EO on biofilm was evaluated by quantifying viable cell number (CFU) and biomass by crystal violet (CV) analysis. The composition of the essential oils was determined by GC / FID and GC / MS. The results showed action against L. monocytogenes, S. aureus and S. Typhimurium with MIC and MBC values of 3.9 µL mL-1, thus showing satisfactory antimicrobial activity, given this was the lowest concentration tested. For the antibiofilm activity, a significant reduction (P < 0.05) was observed for S. typhimurium and S. aureus. Biofilm biomass significantly reduced only for S. aureus and P. aeruginosa. EO presented the geranial and neral isomers as major components.